Investigation of medical students opinions on research fraud in thesis and its frequency - Nouzar Nakhaee; Hadi Nikpour (Kerman University of Medical Sciences, 2005)
Background: Tomorrow doctors or today students should be honest in all the aspects of academic work including conducting a research project and writing the thesis Objective: This study was conducted to explore the prevalence of research fraud among medical students according to their subjective experiences and to clarify the attitudes of them towards the issue Methods: A questionnaire which its reliabiltiy and validity were confirmed was distributed among 104 interns It consisted 7 items concerning major types of research fraud which were determined based upon an extensive literature review and a focus group discussion with interested medical students They were asked about the prevalence of each type of the research misconducts and their prevalence among medical students Results: The response rate was 100% Fifty four percent of the repondents were female Fabrication of data and falsification of the findings were reported to be as high as 37 and 40 percent respectively The subjectively estimated prevalence of plagiarism was between 25 to 50 percent About 58 percent of them approved copying others work whilet 71 percent of them disapproved unethical research behavior towards the patients Conclusion: If the results could be generalized to the whole country they might be regarded as a major educational and ethical problem The result warrant further research and concern about the mandatory research system and alternative approches